THE PRODUCT BACKGROUND AND ASSUMPTIONS (Tufts Archival Research Center, 2007)
Document containing background on the issue of ingredients in cigarettes and accidental fires caused by cigarettes. Describes the objectives of the tobacco industry in relation to these two issues as demonstrating to the public that the tobacco industry is responsible in its use of ingredients and that they need to be kept secret in order to allow the industry to operate in the free market and that the tobacco industry is committed to battling accidental fires from cigarettes. Outlines a series of tactics and strategies to obtain these goals.